BRAIN-GYM (SENAM OTAK) UNTUK MENGATASI PROBLEM BELAJAR ANAK - Sri Suneki; Ririn Ambarini; Dwi Destriani (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2012)
AbstractBrain Gym to maximalise the potensial of the young children in Himpaudi Kecamatan Tembalang is a kind of workshop given to the teachers in order to implement Brain Gym so as to overcome the learning problems of the young children. The materials that are given to the teachers are about how to understand about the concept of Brain Gym, the theories of Brain Gym, the practice of the Brain Gym that is able to give great contribution to overcome the students?óÔé¼Ôäó learning problems. The movement of Brain Gym consists of 26 movements. Brain Gym covers three areas of brain dimention, those are literary, focus, and centralisation. The first part of brain dimention is related to the dimension of left and right brain that has relation with the ability of communication. The second part of brain dimension is related to front and back dimension of the brain that relate to the stem of the brain and it has correlation with the ability of concentration, understanding and interpretation. The last dimension of brain is related to centralisation that has relation with up and down part of the middle part of the brain. It relates to the capability of arranging and organizing something. With the implementation of IbM Brain Gym, it is hoped that the teachers in Himpaudi Kecamatan Tembalang Semarang are proactive enough to implement this kind of gym so as to anticipate and to overcome the learning problems of the students.Key Words: Brain-Gym, Three Dimension of Brain, Literary, Focus, CentralisationAbstrakIpteks yang akan ditransfer kepada HIMPAUDI Kecamatan Tembalang Semarang adalah pelatihan konsep dasar dan teori Brain-Gym. Pelatihan Brain-Gym sangat besar manfaatnya untuk mengatasi problem belajar anak. Senam otak ini terdiri dari 26 gerakan. Brain-Gym atau senam otak meliputi tiga dimensi otak yang utama yaitu lateralitas, fokus, dan pemusatan. Dimensi otak yang pertama yaitu lateralitas terkait dengan dimensi otak kiri dan kanan yang berhubungan dengan kemampuan komunikasi. Dimensi otak yang kedua adalah fokus, terkait dimensi muka-belakang dengan melibatkan batang otak yang berhubungan dengan kemampuan konsentrasi, mengerti, dan memahami. Dimensi otak yang terakhir adalah pemusatan, terkait dimensi atas-bawah dengan melibatkan otak tengah yang berhubungan dengan kemampuan mengatur dan mengorganisasikan sesuatu. Melalui Brain-Gym untuk guru Himpaudi Kecamatan Tembalang, diharapkan para guru dapat menerapkan senam otak ini sebagai bagian dari program kegiatan sekolah yang harus dilaksanakan pada tiap minggunya sebagai bagian dari pelajaran olah raga, sehingga manfaatnya tidak hanya untuk kebugaran siswa tetapi secara tidak langsung juga memberikan manfaat untuk mengatasi problem belajar anak.Kata Kunci: Brain-Gym, Tiga Dimensi Otak, Lateralitas, Fokus, Pemusatan